2012
DOI: 10.1002/pits.20625
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of school‐wide positive behavior support: An exploratory study using single‐case synthesis

Abstract: Positive Behavior Support (PBS) for behavioral problems was included in the 1997 Individuals With Disabilities Education Act reauthorization, reflecting the increased implementation and strengthening empirical evidence for PBS in schools. Whereas PBS can be used reactively, its flexibility has led to a popular comprehensive school‐wide model used for prevention. School‐Wide Positive Behavioral Support (SWPBS) has been used across a variety of school environments and various demographics and has been evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…The current review synthesizes the growing evidence of SWPBIS effects on behavioral, academic, and organizational outcomes and extends prior reviews Mitchell et al, 2018;Solomon et al, 2012) by including unpublished studies and employing a RVE meta-analysis. Overall, we found statistically and educationally significant effects of SWPBIS on all three school-level domains.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The current review synthesizes the growing evidence of SWPBIS effects on behavioral, academic, and organizational outcomes and extends prior reviews Mitchell et al, 2018;Solomon et al, 2012) by including unpublished studies and employing a RVE meta-analysis. Overall, we found statistically and educationally significant effects of SWPBIS on all three school-level domains.…”
Section: Discussionmentioning
confidence: 72%
“…To date, three systematic reviews (i.e., replicable search and inclusion/exclusion procedures) have examined the experimental evidence of the impact SWPBIS has on school, staff, and student outcomes. Solomon, Klein, Hintze, Cressey, and Peller () reviewed single‐case designs and identified 20 studies that included at least one individual component of SWPBIS as an independent variable and student behavior as a dependent variable. The authors used a regression‐based procedure to calculate single‐case design effect sizes and found a small effect ( r 2 = .35).…”
Section: Introductionmentioning
confidence: 99%
“…Although SCD may have been born out of behavior analysis, there is nothing inherent to SCD that prohibits it use in any scientific field so long as the dependent variable in question can be measured repeatedly. In school psychology, SCD is used primarily to provide empirical demonstrations of intervention effectiveness to improve students' academic performance (e.g., Eckert, Ardoin, Daisey, & Scarola, 2000), behavior in the classroom (Solomon, Klein, Hintze, Cressey, & Peller, 2012), and mental health (e.g., Dart et al, 2015); however, SCDs have also been used to study variables such as treatment integrity (Solomon, Klein, & Politylo, 2012) and teacher behavior (e.g., praise; Dufrene, Lestremau, & Zoder-Martell, 2014). Despite its utility, some have suggested that SCD research is underutilized within psychology (Nock et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Within this approach, staff create protective cultures within schools through instruction, redesign of the environment, and attention to systems variables (e.g., policies, team structures, procedures;McIntosh, Filter, Bennett, Ryan, & Sugai, 2009). SWPBS has been found to be effective within individual case studies (Solomon, Klein, Hintze, Cressey, & Peller, 2012) and through randomized control trials (Bradshaw, Mitchell, & Leaf, 2010). The SWPBS approach includes addressing problems across settings, including those outside of the classroom, such as hallways.…”
Section: Schoolwide Positive Behavior Supportmentioning
confidence: 99%